Current Strategies to Modulate Regulatory T Cell Activity in Allergic Inflammation - Bellinghausen, Iris; Khatri, Rahul; Saloga, Joachim (Frontiers in Immunology, 2022)
Over the past decades, atopic diseases, including allergic rhinitis, asthma, atopic dermatitis, and food allergy, increased strongly worldwide, reaching up to 50% in industrialized countries. These diseases are characterized by a dominating type 2 immune response and reduced numbers of allergen-specific regulatory T (Treg) cells. Conventional allergen-specific immunotherapy is able to tip the balance towards immunoregulation. However, in mouse models of allergy adaptive transfer of Treg cells did not always lead to convincing beneficial results, partially because of limited stability of their regulatory phenotype activity. Besides genetic predisposition, it has become evident that environmental factors like a westernized lifestyle linked to modern sanitized living, the early use of antibiotics, and the consumption of unhealthy foods leads to epithelial barrier defects and dysbiotic microbiota, thereby preventing immune tolerance and favoring the development of allergic diseases. Epigenetic modification of Treg cells has been described as one important mechanism in this context. In this review, we summarize how environmental factors affect the number and function of Treg cells in allergic inflammation and how this knowledge can be exploited in future allergy prevention strategies as well as novel therapeutic approaches.